Adapting KOLB’S Experiential Learning Cycle in enhancing attitude and skills among undergraduates through volunteerism - Fazilah Idris,; Wardah Mustafa Din,; Maisarah Tajuddin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Previous studies show that most undergraduates do not participate in volunteering work and hence reduces the opportunity to gain essential skills such as communication, collaboration, creativity and critical thinking. The challenge to develop future-ready graduates is to equip them with the right set of skills and inculcate the right set of attitude. In doing so, experiential learning in a community based-setting would create a distinctive learning environment to achieve the latter. The objective of this research is to identify whether attitude and skills can be enhanced through volunteerism and service. In Universiti Kebangsaan Malaysia (UKM), LMCR1102 Volunteerism and Service Course is offered as an elective subject to all undergraduates. In this course student participates in experiential learning, execute community projects and explore the theories related. Kolb’s Experiential Learning Cycle was adapted as the framework in the development of the curriculum content and approach. This research employs a questionnaire survey which comprises of three sections, and 129 undergraduate participated by purposive sampling. Reflective writings at the end of the course were also analysed, and the results were triangulated with the survey results. From the analysis, there are seven attitudes which students gained during the volunteering work completed in the course which are nobility, responsibility, concern, sincerity, empathy, encouraging others, and sustainability. Among the skills that they acquired are communications skills, collaboration skills and managing diversity. In summary, essential attitude and skills that are pivotal for undergraduates can be gained through volunteering work. This study also highlights that students will continue to participate in volunteer work and community development after graduating.